On the dynamics of an array of spar-buoy oscillating water column devices with inter-body mooring connections. (April 2020) - Oikonomou, C.L.G.; Gomes, R.P.F.; Gato, L.M.C.; Falcão, A.F.O.
Abstract: The performance of an array of floating Oscillating Water Column (OWC) devices, known as spar-buoy OWC, is analysed for a configuration with inter-body mooring connections. This configuration has the potential of being a more economically viable solution due to drastic reductions in the amount of mooring cables, when compared to independently moored configurations. Numerical simulations for an array of independently moored devices and for an unmoored array are presented and compared. The frequency-domain model considered throughout this paper uses linear hydrodynamic and hydrostatic forces; real fluid viscous effects are accounted for by using a linear approximation, while the mooring connections are linearised using perturbation theory. For regular waves, by including an inter-body mooring system, the average heave response amplitude of the array's three buoys decreases by approximately 6 . 8 % at the peak frequency, while the average capture width of the three buoys remains approximately the same. The influence of the wave incidence angle on the array performance is evaluated. A stochastic analysis is conducted to assess the behaviour of the array with mooring connections. A comparative analysis between the performance of an array with inter-body mooring connections and an isolated device suggests a positive park effect for a realistic wave climate. Highlights: A hydrodynamic analysis of a moored array of spar-buoy OWCs is presented. Two different mooring configurations are compared. A stochastic analysis is undertaken for irregular waves. Independent and inter-body moored arrays showed efficiency differences within 2-3%. The average heave RAO of the array decreases by 7.2% after including the moorings.